Hepatocellular Carcinoma: Current Management and Future Development—Improved Outcomes with Surgical Resection - Yoji Kishi; Kiyoshi Hasegawa; Yasuhiko Sugawara; Norihiro Kokudo (International Journal of Hepatology)
Currently, surgical resection is the treatment strategy offering the best long-term outcomes in patients with hepatocellular carcinoma (HCC). Especially for advanced HCC, surgical resection is the only strategy that is potentially curative, and the indications for surgical resection have expanded concomitantly with the technical advances in hepatectomy. A major problem is the high recurrence rate even after curative resection, especially in the remnant liver. Although repeat hepatectomy may prolong survival, the suitability may be limited due to multiple tumor recurrence or background liver cirrhosis. Multimodality approaches combining other local ablation or systemic therapy may help improve the prognosis. On the other hand, minimally invasive, or laparoscopic, hepatectomy has become popular over the last decade. Although the short-term safety and feasibility has been established, the long-term outcomes have not yet been adequately evaluated. Liver transplantation for HCC is also a possible option. Given the current situation of donor shortage, however, other local treatments should be considered as the first choice as long as liver function is maintained. Non-transplant treatment as a bridge to transplantation also helps in decreasing the risk of tumor progression or death during the waiting period. The optimal timing for transplantation after HCC recurrence remains to be investigated.